Avicenna’s Canon of Medicine and Modern Urology. Part III: Other Bladder Diseases - Madineh, Seyed Mohammad Ali (Urology Journal, 2009)
In the third part of this article on Avicenna’s Canon of Medicine, diseases of the bladder other than bladder calculus are reviewed. Avicenna covers topic on bladder infection, pelvic abscess, urethritis, cystitis, prostatitis, bladder tumors, bladder dysfunction, urinary retention, and neurogenic bladder. The interesting point is that 10 centuries ago, Avicenna had described almost all diseases of the blabber. Avicenna’s Canon of Medicine is a comprehensive book on semiology of bladder diseases. His approach to diagnoses complies with the modern methodology, and even in some interventions such as routes of drug administration and catheterization, his points are astonishing.